Improvement of diabetes-induced metabolic syndrome by millet prolamin is associated with changes in serum metabolomics. (December 2021) - Fu, Yongxia; Zhang, Fan; Liu, Zhenyu; Zhao, Qingyu; Xue, Yong; Shen, Qun
Abstract: Even though the beneficial effect of millet prolamin on diabetes has been demonstrated previously, the underlying mechanism has not yet been researched. The current study aims to evaluate whether millet prolamin supplementation could improve diabetes by modulating serum metabolite disorders. Diabetes was induced in male C57BL/6J mice using a high-fat diet (HFD) and streptozotocin (STZ). Then the diabetic mice were randomly assigned to the HFD/STZ and HFD/STZ-prolamin groups and then administrated with saline or prolamin for five weeks by gavage. Our results showed that prolamin administration alleviated body weight loss, mitigated glucose homeostasis disorder, which manifested a decreased fasting plasma glucose level by 14.21% and an increased homeostasis model assessment-β cell function (HOMA-β) index by 24.86%, and alleviated liver function impairment by downregulating alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in diabetic mice. Metabolomics analysis indicated that serum metabolite disturbance caused by diabetes was partially alleviated by prolamin administration. Notably, retinol metabolism and riboflavin metabolism are the two pathways that contributed the most to the anti-diabetic effect of prolamin. Collectively, the hypoglycemic effect of millet prolamin can be associated with the serum metabolic profile alterations. Graphical abstract: Image 1 Highlights: Millet prolamin has hypoglycemic function. Serum metabolite alterations were related to the anti-diabetic effect of millet prolamin. Retinol metabolism and riboflavin metabolism contributed the most to the anti-diabetic effect of millet prolamin.